A configuração da memória nacional na mídia televisual contemporânea - Fonseca, Elisa Vieira (2017)
The following work intends to examine how contemporary media, particularly television, is recovering the memory of Brazilian society and building characteristic features of a national memory, in relation to certain periods in the country‟s history. Therefore, the research has as its main objective to observe how contemporary television sets Brazilian‟s memory in narratives that address the period of military dictatorship. Through which themes and discursive strategies do their narratives articulate the history and memory of the society of that period? Keeping in mind the general objective and the questions raised, the following specific objectives were established: (1) recover the historical context, as well as television‟s operating mode, during the period in which the country was under the regime of the military dictatorship (1964-1985), through the specialized bibliography in sociology and history; (2) characterize selected televisual programs, examining their ways of structuring, central themes and developments, through its production instances and ways of broadcasting; (3) analyze selected programs from the standpoint of their relations, for inter and intratextual; (4) identify discursive strategies and expressive mechanisms used in the representation of the Brazilian memory, through the configuration of characters, characterization of scenarios and toning. The analysis is based on discursive semiotics of European inspiration, as formulated by Hjelmslev (1975) and Greimas (1979), and invites other scholars, whose works are specifically directed to the examination of television. The work also seeks foundations in theoreticians who reflect on issues related to identity construction and national identity, memory and history of Brazilian television.